Analisis Pola Persebaran Fasilitas Sosial Di Kabupaten Penajam Paser Utara - Lestari, Astri; Dewanti, Ajeng Nugrahaning; Astha, Dwinsani Pratiwi; Pratama, Maryo Inri (COMPACT: Spatial Development Journal, 2024)
Indonesia, as a country with a wide population diversity, faces the challenge of significant population growth. Rapid population growth requires increased social facilities to support the population's quality of life. According to Bapelibang PPU, the pattern of distribution of social facilities in this district is still not able to serve the entire community so there are still people who have difficulty getting these social facility services. Therefore, it is feared that this pattern of uneven distribution of social facilities will become a serious problem in the future. To overcome this, research is needed regarding the analysis of the distribution patterns of social facilities in order to provide consideration for future regional development so that it can maximize the function of services to the community. The aim of this research is to determine the distribution pattern of social facilities in North Penajam Paser Regency. The research method used in this research is descriptive quantitative with the nearest neighbor analysis method. The results of this analysis were obtained in this district. The distribution patterns that were formed tended to form clustered and random patterns.